Multiple exemplar instruction and integration of listening and speaking behaviors with substantive-adjective syntactic units in children with ANSD and CI - Barboza Merlin, Adriana Maura [UNESP]; Moreira Almeida-Verdu, Ana Claudia [UNESP]; das Neves, Anderson Jonas; Nascimento Silva, Leandra Tabanez do; Mortari Moret, Adriane Lima (Soc Brasileira Fonoaudiologia, 2019)
Purpose: To verify the effect of the multiple exemplar instruction at the acquisition and integration of listening and speaking behaviors, with substantives and substantive-adjective combinations, in children with Auditory Neuropathy Spectrum Disorder (ANSD) and cochlear implant (CI). Methods: Participants were two children with ANSD that were users of CL We adopted dictated stimulus and pictures that corresponded to words (substantive) and substantive-adjective syntactic units. The study was arranged in teaching steps that were intercalated with listening and speaking behaviors probes, with all stimuli. The multiple exemplar instruction presented oral imitation (echoic). auditory recognition (listening) and pictures naming (touch) tasks, on a rotating way; the substantives were taught first and, idler that, the substantive-adjective combinations. Results: In the pre-test, the participants showed variability and discrepancy in the correct responses percentages of listening and speaking. All achieved firstly 100% correct responses in the listening task and the speaking performances were close to listening alter the teaching. All extended substantive learning to substantive-adjective syntactic units. Conclusion: Children with ANSD and CI can learn and integrate listening and speaking behaviors by multiple exemplar instruction, from words to syntactic units.
Keywords: Hearing Loss; Cochlear Implant; Teaching; Verbal Learning; Rehabilitation